Analysis of Students’ Self-Regulated Learning on Prospective Elementary School Teachers’ Gender Differences - Roy Ardiansyah; Munawir Yusuf; Subagya Subagya; Idam Ragil Widianto Atmojo (AL-ISHLAH: Jurnal Pendidikan, 2023)
Eliminating gender in education is one of the SDGs’ (Sustainable Development Goals) targets in which previous research has examined gender in its correlation to achievement, learning outcomes, learning processes, and learning styles. One thing that is necessary but has not been investigated by previous researchers is the factor causing the differences in the correlation significance in the form of ways of learning and self-awareness as part of Self-Regulated Learning. This research was conducted to investigate the causal relationship between the Self-Regulated Learning of the students of the Department of Primary School Teacher Education of a state university in Surakarta in the 2022/2023 academic year and their genders. This research used a quantitative approach with a comparative research type. The population in this study were all the students of the Department of Primary School Teacher Education in the 2022/2023 academic year using Cluster Random Sampling as a sampling technique. Data collection techniques used closed and direct questionnaires. The data analysis technique used was descriptive statistical analysis and inferential statistical analysis. Based on the calculation results of the Independent Sample T-Test, a significant value of 0.267 0.05 was obtained, and the t count was 1.125 F table of 1.717. The results showed that the Self-Regulated Learning ability of the students of the Department of Primary School Teacher Education in the 2022/2023 academic year has the same average, so the ability of Self-Regulated Learning cannot be differentiated according to gender.